Preparation method and application of uric acid and pH dual-electrode detection sensor
By fabricating a dual-electrode sensor for uric acid and pH using Mn2O3/Fe2O3 material and gold nanolayers, the problems of real-time detection and pH influence in uric acid detection were solved, achieving high sensitivity and stable simultaneous detection of uric acid and pH, which is suitable for wearable sensors for sweat.
Patent Information
- Application Number
- CN202511264283.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-18
AI Technical Summary
Existing uric acid testing methods rely on invasive and complex instruments, making real-time monitoring impossible. Furthermore, the concentration of uric acid in sweat is low and easily affected by pH changes, and there is a lack of effective solutions for simultaneously detecting uric acid and pH.
Using Mn2O3/Fe2O3 material as the core of the sensor chip, combined with uric acid oxidase and gold nanolayer, a dual-electrode sensor for uric acid and pH is prepared by electrodeposition technology. By utilizing the high specific surface area and conductivity of Mn2O3/Fe2O3 and the pH sensitivity of polyaniline, the simultaneous detection of uric acid and pH can be achieved.
It achieves highly sensitive detection of low concentrations of uric acid, can monitor uric acid concentration in sweat in real time and calibrate pH value, improves the reliability and stability of detection, and has anti-interference capabilities.
Smart Images

Figure CN120971529A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biological detection sensor technology, and relates to a method for preparing and applying a dual-electrode detection sensor for uric acid and pH. Background Technology
[0002] With the continuous improvement of people's living standards, preventive medicine is receiving increasing attention in the management of chronic diseases. The levels of metabolites are closely related to human health, and persistent deviations in metabolites can serve as indicators for disease assessment. Uric acid is the final product of purine metabolism in the human body, with a normal range of 130-460 μM in the blood. Excessively high uric acid levels can cause gout, and abnormal uric acid concentrations are also associated with cardiovascular disease, type 2 diabetes, and kidney disease. By monitoring uric acid levels, the onset of hyperuricemia can be predicted in advance, allowing for interventions through diet and medication to prevent gout attacks. Currently, the gold standard for uric acid testing relies on invasive and intermittent blood sampling and requires sophisticated instruments (such as gas chromatography-mass spectrometry), which cannot meet the needs of real-time monitoring.
[0003] There is a positive correlation between sweat and blood uric acid levels. However, the concentration of uric acid in sweat is about five times lower than in blood, ranging from only 0.02 to 0.1 mM. Furthermore, the detection of uric acid in sweat is often easily affected by pH changes (5.5-8.0), impacting accuracy. Therefore, developing sensors capable of simultaneously detecting uric acid and pH is crucial. However, no ideal solution has yet been reported. Summary of the Invention
[0004] This invention addresses the problems existing in traditional sweat uric acid detection by proposing a novel method for preparing and applying a dual-electrode sensor for uric acid and pH detection.
[0005] To achieve the above objectives, the present invention is implemented using the following technical solution: A method for preparing a dual-electrode sensor for detecting uric acid and pH, comprising the following steps: (1) Add soluble manganese salt and complexing agent to water, mix evenly to obtain mixture A, add soluble ferricyanide salt solution B, age and stand at room temperature, centrifuge and dry to obtain MnFe PBA material.
[0006] (2) MnFe PBA material was pyrolyzed at high temperature in air atmosphere to obtain Mn2O3 / Fe2O3 material.
[0007] (3) Using conductive carbon paste as the first working electrode, the second working electrode and the counter electrode, and silver / silver chloride as the reference electrode, a dual working electrode sensor chip is obtained by screen printing. Mn2O3 / Fe2O3 material is added to deionized water and mixed evenly to obtain a dispersion. The dispersion is drop-coated onto the surface of the first working electrode, and then a mixture containing crosslinking agent and uric acid oxidase, M, is added drop-coated. Chloroauric acid solution and hydrochloric acid solution are mixed to obtain electrodeposition solution C. Aniline solution and hydrochloric acid solution are mixed evenly to obtain electrodeposition solution D. Electrodeposition solutions C and D are sequentially applied to the second working electrode. After electrodeposition, the electrodeposition solution is placed in a 4°C refrigerator for low-temperature drying to obtain a pH and uric acid dual electrode sensor.
[0008] Preferably, in step (1), the soluble manganese salt is manganese chloride or manganese sulfate, the concentration of soluble manganese salt in the mixture A is 5-50 mM, the volume ratio of the mixture A to the soluble ferricyanide solution B is 1:1, the soluble ferricyanide is potassium ferricyanide or sodium ferricyanide, and the molar ratio of soluble manganese salt to soluble ferricyanide is (0.3-3):1.
[0009] Preferably, in step (1), the complexing agent is either ethylenediaminetetraacetic acid or sodium citrate, and the molar ratio of the complexing agent to the soluble manganese salt is (0.5-2):1; the aging and standing time is 6-24h.
[0010] Preferably, the pyrolysis temperature in step (2) is 200-400℃ and the pyrolysis time is 2-4h.
[0011] Preferably, in step (3), the concentration of chloroauric acid solution in electrodeposition solution C is 40-60 mM, the concentration of hydrochloric acid solution is 40-60 mM, the molar ratio of chloroauric acid to hydrochloric acid in electrodeposition solution C is 1:1, and the crosslinking agent is any one of chitosan, carboxymethyl chitosan, glutaraldehyde, or Nafion.
[0012] Preferably, in step (3), the concentration of aniline solution D in the electrodeposition solution is 50-100mM, the concentration of hydrochloric acid solution is 50-100mM, the molar ratio of aniline to hydrochloric acid in electrodeposition D is 1:1, the voltage for electrodeposition of electrodeposition solution C on the second working electrode is -0.1-0.1V, and the deposition method is to deposit for 20-30s using chronoamperometry, and the voltage for electrodeposition of electrodeposition solution D on the second working electrode is -0.2V-1V, and the deposition method is to deposit for 20-30 times using cyclic voltammetry at a rate of 90-110mV / s.
[0013] This invention proposes the application of the sensor prepared by the above method in the real-time detection of uric acid and pH in sweat.
[0014] The structure of the Mn2O3 / Fe2O3 sensing material prepared in this invention plays a crucial role in the detection performance of uric acid. Due to the low specific surface area and poor electron transport capability of Prussian blue, directly using it in the construction of uric acid detection chips cannot achieve ideal detection performance and cannot meet practical detection requirements. This invention introduces a complexing agent as a kinetic modifier during the preparation process, successfully obtaining a hollow MnFe PBA precursor. This structure significantly increases the specific surface area of the material, shortens the ion / electron transport path, thereby enhancing the current response. Simultaneously, the regulated Mn2O3 / Fe2O3 exhibits a high-roughness surface morphology, effectively expanding the number of active sites and greatly improving the material's electrocatalytic ability for uric acid. Furthermore, the precursor, after pyrolysis into metal oxides, further promotes charge transfer kinetics and significantly improves the material's conductivity. By drop-coating a uricase-containing solution, uric acid can specifically react with uricase oxidase to generate hydrogen peroxide; subsequently, Mn2O3 / Fe2O3 undergoes a redox reaction with hydrogen peroxide to generate an electrical signal, thereby achieving high-performance detection of uric acid. In pH sensing, polyaniline, as the core sensing material, undergoes a redox transformation with changes in solution pH, resulting in a change in open-circuit potential with pH. Gold nanolayers, serving as a high-performance conductive substrate and structural support, possess excellent conductivity, chemical stability, and high specific surface area, promoting efficient electron transfer and thus optimizing the overall performance of the pH sensor. In summary, the Mn₂O₃ / Fe₂O₃-based sensing chip prepared in this invention exhibits excellent electrocatalytic activity and electron transfer efficiency, enabling the identification and real-time monitoring of low concentrations of uric acid in sweat.
[0015] Compared with the prior art, the advantages and positive effects of the present invention are as follows: 1. This invention is based on electrochemical biosensing technology. A highly sensitive uric acid sensing chip is obtained by preparing high-performance Mn2O3 / Fe2O3 materials, which exhibits excellent electrochemical sensing performance for low concentrations of uric acid.
[0016] 2. This invention integrates a pH sensor to continuously track the pH value of sweat while detecting uric acid. By studying the relationship between the pH value and uric acid concentration, the uric acid response is calibrated, thereby improving the reliability of uric acid monitoring.
[0017] 3. This dual-function chip exhibits high sensitivity, long-term stability, reproducibility, and good anti-interference ability for uric acid in a real sweat environment. Attached Figure Description
[0018] Figure 1 This is a scanning electron microscope image of Mn2O3 / Fe2O3.
[0019] Figure 2 This is a physical image of a dual-working-electrode chip.
[0020] Figure 3 This is a fitted curve for uric acid detection.
[0021] Figure 4 This is a fitted curve for pH value detection.
[0022] Figure 5 The curves show the response of uric acid concentration at different pH levels.
[0023] The labels in the attached figures are as follows: 1 is the counter electrode, 2 is the first working electrode, 3 is the second working electrode, and 4 is the reference electrode. Detailed Implementation
[0024] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described below with reference to specific embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0025] Numerous specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways than those described herein, and therefore the invention is not limited to the specific embodiments disclosed in the following specification.
[0026] Example 1 This embodiment provides a method for preparing a dual-electrode sensor for detecting uric acid and pH, the steps of which are as follows.
[0027] (1) Preparation of MnFe PBA material: Prepare 100 mL each of MnFe PBA synthesis solution A and synthesis solution B. Synthesis solution A is a mixture of manganese sulfate and sodium citrate, with a molar concentration of 10 mM for manganese sulfate and 20 mM for sodium citrate. The preparation method is as follows: weigh manganese sulfate and sodium citrate and add them to about 50 mL of deionized water, then make up to 100 mL with deionized water, and stir at 200 rpm for 30 min to obtain a uniform dispersion. Then add synthesis solution B, which is a 3.3 mM potassium ferricyanide aqueous solution, and then age and stand at room temperature for 24 h. After the reaction is completed, centrifuge the reaction solution at 8000 rpm for 6 min, scrape off the solid obtained by centrifugation, and dry it in an oven at 60℃ for 12 h to obtain MnFe PBA material.
[0028] (2) Preparation of Mn2O3 / Fe2O3 material: The MnFe PBA material from step (1) was placed in a muffle furnace and heated to 300℃ at a rate of 4℃ / min in air atmosphere, and maintained at 300℃ for 3h for high-temperature pyrolysis. After pyrolysis, it was naturally cooled to room temperature. The powder obtained after the pyrolysis reaction was collected, which is the Mn2O3 / Fe2O3 material. Its SEM characterization results are attached. Figure 1As shown in the figure, Mn2O3 / Fe2O3 has a highly rough surface morphology, which effectively increases the number of active sites and enhances the material's electrocatalytic ability for uric acid.
[0029] (3) Fabrication of the dual-working-electrode chip: The Mn2O3 / Fe2O3 material from step (2) was uniformly dispersed in deionized water to prepare a 4 mg / mL dispersion. Then, 30 μL of the dispersion was dropped onto the first working electrode 2 region of the screen-printed chip. Subsequently, 10 μL of a mixed aqueous solution containing chitosan and uricase was dropped onto the chip. The concentration of chitosan was 5 mg / mL, and the concentration of uricase was 5 U / μL. The second working electrode 3 was electrodeposited in an aqueous mixture of 50 mM chloroauric acid and 50 mM hydrochloric acid using a chronoamperometry method at 0 V for 30 s. Then, the second working electrode 3 was electrodeposited again in a mixed aqueous solution containing 100 mM aniline and 100 mM hydrochloric acid using a cyclic voltammetry method from -0.2 V to 1 V at a rate of 100 mV / s for 25 times. Finally, the dual working electrode chip was dried in a refrigerator at 4 °C for 12 h to obtain a uric acid and pH dual electrode sensor.
[0030] The uric acid and pH detection performance of the chip was tested using the chronoamperometry and open-circuit potential method on a Shanghai Chenhua CHI660E electrochemical workstation at an operating voltage of 0.5V. The three electrodes of the printed chip—two working electrodes, reference electrode 4 (Ag / AgCl electrode), and counter electrode 1—were connected to the corresponding electrode lines on the electrochemical workstation, with the electrode areas immersed in the detection system. The results showed that the dual-working-electrode chip achieved a sensitivity of 30.42 μA·mM for uric acid. -1 ·cm -2 The linear range is 0.0025-2.335 mM; the pH sensitivity is up to 51.70 mV·pH. -1 The detection range is 4-8, enabling dynamic feedback for uric acid and pH. After detection, the chip was stored in PBS buffer solution at 4℃ for 12 hours, and the response signal was 93% of the initial signal, indicating that the dual-working-electrode chip has excellent stability.
[0031] Example 2 Unless otherwise specified, the conditions in this embodiment and subsequent embodiments are the same as in Embodiment 1. This embodiment provides a method for preparing a dual-electrode sensor for uric acid and pH detection, the steps of which are as follows.
[0032] 100 mL each of MnFePBA synthesis solution A and synthesis solution B were prepared. Synthesis solution A was a mixture of manganese chloride and ethylenediaminetetraacetic acid (EDTA), with a manganese chloride concentration of 5 mM and a molar ratio of manganese chloride to EDTA of 0.5:1. After bringing the mixture to a final volume, the solution was stirred at 200 rpm for 30 min to obtain a uniform dispersion. Then, synthesis solution B was added. Synthesis solution B was a 15 mM potassium ferricyanide aqueous solution. Both solutions A and B were dissolved in deionized water. The reaction mixture was aged and allowed to stand at room temperature for 12 h. After the reaction was completed, the reaction solution was centrifuged at 6000 rpm for 6 min. The solid obtained by centrifugation was dried at 60 °C for 12 h to obtain the MnFePBA material.
[0033] (2) Preparation of Mn2O3 / Fe2O3 material: The MnFe PBA material from step (1) was placed in a muffle furnace and pyrolyzed at 200℃ for 2 hours in an air atmosphere, with a heating rate of 2℃ / min. The powder obtained after the pyrolysis reaction was collected, which is the Mn2O3 / Fe2O3 material.
[0034] (3) Fabrication of the dual-working-electrode chip: The Mn2O3 / Fe2O3 material from step (2) was uniformly dispersed in deionized water to prepare a 2 mg / mL dispersion. Then, 30 μL of the dispersion was dropped onto the first working electrode 2 of the screen-printed chip. Subsequently, 10 μL of a mixture containing chitosan and uricase was dropped onto the chip. The concentration of chitosan was 5 mg / mL and the concentration of uricase was 5 U / μL. Then, the second working electrode 3 was electrodeposited in a mixture of 40 mM chloroauric acid and 40 mM hydrochloric acid. The electrodeposition was performed at 0 V for 20 s using chronoamperometry. Then, the second working electrode 3 was electrodeposited in a mixture of 50 mM aniline and 50 mM hydrochloric acid. The electrodeposition was performed 25 times at a rate of 90 mV / s from -0.2 V to 1 V using cyclic voltammetry. Finally, the dual working electrode chip was dried in a refrigerator at 4 °C for 12 h to obtain the uric acid and pH sensor.
[0035] Testing showed that the dual-working-electrode chip prepared in this embodiment has a sensitivity of 28.43 μA·mM to uric acid. -1 ·cm -2 The linear range is 0.004-2.0 mM, and the pH sensitivity is up to 50.4 mV·pH. -1 The detection range is 5-8, enabling dynamic feedback for uric acid and pH. After testing, the chip was stored in PBS buffer solution at 4°C for 12 hours, and the response signal was 92% of the initial signal, indicating that the dual-electrode chip has excellent stability.
[0036] Example 3 This embodiment provides a method for preparing a dual-electrode sensor for detecting uric acid and pH, the steps of which are as follows.
[0037] (1) Preparation of MnFe PBA material: 100 mL each of MnFe PBA synthesis solution A and synthesis solution B were prepared. Synthesis solution A was a mixture of manganese sulfate and ethylenediaminetetraacetic acid (EDTA), with a manganese sulfate concentration of 30 mM and a molar ratio of 1:1. After adjusting the volume, the mixture was stirred at 200 rpm for 30 min to obtain a uniform dispersion. Then, synthesis solution B was added. Synthesis solution B was a 30 mM sodium ferricyanide aqueous solution. The solvent for both solutions A and B was deionized water. The reaction was allowed to stand at room temperature for 18 h. After the reaction was completed, the reaction solution was centrifuged at 4000 rpm for 6 min and then dried in an oven at 60 °C for 12 h to obtain MnFe PBA material.
[0038] (2) Preparation of Mn2O3 / Fe2O3 material: The MnFe PBA material from step (1) was placed in a muffle furnace and subjected to high-temperature pyrolysis at 400℃ for 2.5h in an air atmosphere, with a heating rate of 3℃ / min. The powder obtained after the pyrolysis reaction was collected, which is the Mn2O3 / Fe2O3 material.
[0039] (3) Fabrication of the dual-working-electrode chip: The Mn2O3 / Fe2O3 material from step (2) was uniformly dispersed in deionized water to prepare a 3 mg / mL dispersion. Then, 30 μL of the dispersion was dropped onto the first working electrode 2 of the screen-printed chip. Subsequently, 10 μL of a mixture containing chitosan and uricase was dropped onto the chip. The concentration of chitosan was 5 mg / mL and the concentration of uricase was 5 U / μL. Then, the second working electrode 3 was electrodeposited in a mixture of 60 mM chloroauric acid and 60 mM hydrochloric acid. The electrodeposition was performed at 0.1 V for 30 s using chronoamperometry. Subsequently, the second working electrode 3 was electrodeposited in a mixture of 80 mM aniline and 80 mM hydrochloric acid. The electrodeposition was performed 25 times at a rate of 110 mV / s from -0.2 V to 1 V using cyclic voltammetry. After drying the dual working electrode chip in a refrigerator at 4 °C for 12 h, the uric acid and pH sensors were obtained.
[0040] Testing showed that the dual-working-electrode chip prepared in this embodiment has a sensitivity of 29.13 μA·mM to uric acid. -1 ·cm -2 The linear range is 0.01-2.3 mM, and the pH sensitivity is up to 52.0 mV·pH. -1The detection range is 5-8, enabling dynamic feedback for uric acid and pH. After testing, the chip was stored in PBS buffer solution at 4°C for 12 hours, and its response signal was 91% of the initial signal, indicating that the dual-working-electrode chip has excellent stability.
[0041] 1. Uric acid fitting curve Uric acid was dissolved in a 1M NaOH aqueous solution, heated to 65°C, and stirred for 10 minutes to prepare uric acid solutions of different concentrations. The dual-working-electrode chip prepared in Example 1 was used to detect uric acid at different concentrations. The contacts of the three electrodes of the printed chip—two working electrodes, a reference electrode, and a counter electrode—were connected to the corresponding electrode lines on an electrochemical workstation, with the electrode areas immersed in the detection system (pH 6.5). Subsequently, uric acid solutions of different concentrations were added to the detection system, and the current change was detected using a chronoamperometry method. The detected current and uric acid concentration were linearly fitted, and the results are shown in the attached figure. Figure 3 As shown.
[0042] 2. pH fitting curve The pH of the detection system was adjusted to 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, and 8 using 1M HCl and 1M NaOH. The dual-working-electrode chip prepared in Example 1 was used to detect the systems at different pH values. The contacts of the three electrodes of the printed chip—working electrode, reference electrode, and counter electrode—were connected to the corresponding electrode lines on an electrochemical workstation, and the electrode areas were immersed in the detection systems at different pH values. The potential change was detected using the open-circuit potential method. The detected voltage and pH values were linearly fitted, and the results are shown in the appendix. Figure 4 As shown.
[0043] from Figure 3 and Figure 4 It can be seen that there is a good linear relationship between the response current of the first working electrode and the uric acid concentration, and between the voltage of the second working electrode and the pH value, which can simultaneously realize the quantitative detection of uric acid and pH.
[0044] 3. Fitted curves of uric acid at different pH levels The pH of the detection system was adjusted to 5, 6, 7, and 8 using 1M HCl and 1M NaOH. Uric acid was detected in the detection system at pH 5, 6, 7, and 8 using the dual-working-electrode chip prepared in Example 1. The uric acid detection current was linearly fitted to the uric acid concentration. The sensitivities for uric acid detection at pH 5, 6, 7, and 8 were 16.69, 22.62, 31.00, and 12.89 μA·mM, respectively. -1 ·cm -2Based on this test result, in the actual uric acid testing process, response curves between the first working current and uric acid concentration at different pH levels can be generated, such as... Figure 5 The response curve allows for linear fitting of the response current and uric acid concentration. Then, the pH value of the sweat sample is measured using a second working electrode, and the corresponding fitting curve is selected based on this value. The current response value measured by the first working electrode is substituted into this fitting curve to calculate the corrected uric acid concentration, thus improving the accuracy of the detection.
[0045] 4. Real sample testing Sweat samples were collected from three subjects during exercise and labeled as Sample 1, Sample 2, and Sample 3. Table 1 shows the uric acid detection results of the three sweat samples using the dual-working-electrode chip prepared in Example 1. The actual values are the results detected by high-performance liquid chromatography (HPLC) (Agilent 1260). Table 2 shows the pH detection results of the three sweat samples using the dual-working-electrode chip of Example 1. The actual values are the results detected by a pH meter (METTLER TOLEDO).
[0046] Table 1. Detection results of uric acid in three sweat samples using a dual-electrode chip. Table 2. pH detection results of three sweat samples using a dual-electrode chip. As shown in Tables 1 and 2, the dual-electrode detection sensor prepared in Example 1 yields detection results for uric acid and pH in real sweat that are not significantly different from those of traditional large-scale instruments. Furthermore, pH and uric acid can be detected simultaneously without signal interference. Due to individual differences in metabolism and exercise intensity, sweat pH values can fluctuate considerably, and the pH of the testing environment can affect the electrochemical signal for uric acid detection, directly impacting accuracy. In actual uric acid detection, the second working electrode is used to detect the pH value of the sweat sample, and a corresponding fitting curve is selected based on this value. The current response value measured by the first working electrode is substituted into this fitting curve to calculate the corrected uric acid concentration. Therefore, simultaneous detection of uric acid and pH in sweat provides a more accurate uric acid concentration detection result. This dual-electrode sensor achieves simultaneous detection of uric acid and pH, solving the problems of low uric acid concentration and susceptibility to pH fluctuations in actual sweat detection, thus enabling accurate detection of uric acid in sweat and holding promise for integration into wearable sweat sensors.
[0047] Comparative Example 1 The difference between this comparative example and Example 1 is that the MnFe PBA material is not subjected to pyrolysis treatment and is directly used as the chip modification material, while other conditions remain unchanged. Experimental verification shows that the dual-working-electrode chip based on MnFe PBA has almost no response to uric acid and cannot meet practical detection requirements.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that no complexing agent was added to mixture A, while all other conditions remained unchanged. Experimental verification showed that the dual-electrode chip prepared based on this material had a weak response signal to uric acid, with a sensitivity of only 18.40 μA·mM. -1 ·cm -2 The detection range is 0.04mM-1.8mM, which cannot meet the actual detection needs.
[0049] Comparative Example 3 The difference between this comparative example and Example 1 is that the step of electrodepositing the second working electrode with a mixture of chloroauric acid and hydrochloric acid is omitted, while the other conditions remain unchanged. Experimental verification shows that the pH sensitivity of the polyaniline-based dual-working-electrode chip is only 25.4 mV·pH. -1 The detection range is 5-7, which is significantly lower than the pH performance of the chip in Example 1, fully demonstrating that the modification of the gold nanolayer plays a key role in pH detection.
[0050] Comparative Example 4 The difference between this embodiment and Embodiment 1 is that the step of electrodepositing the second working electrode with a mixture of aniline and hydrochloric acid is omitted, while the other conditions remain unchanged. Experimental verification shows that the dual-working-electrode chip based solely on the gold nanolayer has almost no pH response and cannot meet practical detection requirements.
[0051] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing a dual-electrode sensor for detecting uric acid and pH, characterized in that, The steps are as follows: (1) Add soluble manganese salt and complexing agent to water, mix evenly to obtain mixture A, add soluble ferricyanide salt solution B, age and stand at room temperature, centrifuge and dry to obtain MnFe PBA material; (2) MnFe PBA material was pyrolyzed at high temperature in air atmosphere to obtain Mn2O3 / Fe2O3 material; (3) Using conductive carbon paste as the first working electrode, the second working electrode and the counter electrode, and silver / silver chloride as the reference electrode, a dual working electrode sensor chip is obtained by screen printing; Mn2O3 / Fe2O3 material is added to deionized water and mixed evenly to obtain a dispersion, the dispersion is drop-coated onto the surface of the first working electrode, and then a mixture containing crosslinking agent and uric acid oxidase M is added drop-coated. Chloroauric acid solution and hydrochloric acid solution are mixed to obtain electrodeposition solution C; aniline solution and hydrochloric acid solution are mixed evenly to obtain electrodeposition solution D. Electrodeposition solutions C and D are sequentially applied to the second working electrode. After electrodeposition, the electrodeposition solution is dried at low temperature to obtain a pH and uric acid dual-electrode sensor.
2. The uric acid and pH dual-electrode detection sensor according to claim 1, characterized in that, In step (1), the soluble manganese salt is manganese chloride or manganese sulfate. The concentration of soluble manganese salt in the mixed solution A is 5-50 mM. The volume ratio of mixed solution A to soluble ferricyanide solution B is 1:
1. The soluble ferricyanide salt is potassium ferricyanide or sodium ferricyanide. The molar ratio of soluble manganese salt to soluble ferricyanide salt is (0.3-3):
1.
3. The uric acid and pH dual-electrode detection sensor according to claim 1, characterized in that, In step (1), the complexing agent is either ethylenediaminetetraacetic acid or sodium citrate, and the molar ratio of the complexing agent to the soluble manganese salt is (0.5-2):1; the aging and standing time is 6-24h.
4. The uric acid and pH dual-electrode detection sensor according to claim 1, characterized in that, In step (2), the pyrolysis temperature is 200-400℃ and the pyrolysis time is 2-4h.
5. The uric acid and pH dual-electrode detection sensor according to claim 1, characterized in that, In step (3), the concentration of chloroauric acid solution C in electrodeposition solution C is 40-60 mM, the concentration of hydrochloric acid solution is 40-60 mM, the molar ratio of chloroauric acid to hydrochloric acid in electrodeposition solution C is 1:1, and the crosslinking agent is any one of chitosan, carboxymethyl chitosan, glutaraldehyde or Nafion.
6. The uric acid and pH dual-electrode detection sensor according to claim 1, characterized in that, In step (3), the concentration of aniline solution D is 50-100mM, the concentration of hydrochloric acid solution is 50-100mM, the molar ratio of aniline to hydrochloric acid in electrodeposition solution D is 1:1, the voltage for electrodeposition of electrodeposition solution C on the second working electrode is -0.1-0.1V, and the deposition method is chronoamperometry for 20-30s; the voltage for electrodeposition of electrodeposition solution D on the second working electrode is -0.2V-1V, and the deposition method is cyclic voltammetry at a rate of 90-110mV / s for 20-30 times.
7. The application of the sensor prepared by any one of claims 1-6 in a self-calibrating wearable device for real-time monitoring of sweat uric acid and pH.